Personalised Treatment Plan for Diabetes Using Machine Learning (International Journal of Engineering and Computer Science, 2025)
One major worldwide health concern is diabetes, achronic illness marked by high blood glucose levels. Diabeteshas always been managed in a traditional manner, but newdevelopments in technology and medical research highlight thenecessity of individualized treatment programs to maximizepatient outcomes. Individual patient characteristics, includinggenetic predispositions, lifestyle, health problems, age, and par-ticular glucose metabolism patterns, are taken into considerationin a personalized treatment plan (PTP) for diabetes. This strategymakes it possible to implement specialized interventions, such asfood advice, medication schedules, ongoing glucose monitoring,and behavioral changes. Personalized treatments concentrate onreducing problems and enhancing general quality of life in addi-tion to better management. The accuracy of these individualizedapproaches has been further improved by the incorporationof big data, genetics, and artificial intelligence into diabetesmanagement. The significance of customized treatment plans fordiabetes management is emphasized in this abstract, as is theirpotential to completely transform existing treatment paradigmsby offering more efficient and patient-centered care.